Does the presence of persistant metopic suture affect the use of frontal sinus and frontal morphometric measurements in gender identification? - Say, Ayşe; Okur, Nazan (The European Research Journal, 2025)
Objectives: One structure capable of use for gender estimation in forensic science is the frontal bone. This study used computed tomography (CT) and investigated whether frontal sinus and frontal morphometric measurements could also be used to identify gender in people with persistent metopic suture (PMS). Methods: Nine hundred ninety-one patients who underwent brain-paranasal sinus CT for any reason were divided into two groups, PMS and non-PMS. The presence and volume of both halves of the frontal sinus, frontal morphometric measurements including minimum-maximum frontal width, and frontal bone surface length on the outer table surface between the coronal sutures in the axial section were measured. Results: In the non-PMS group, all quantitative parameters (frontal sinus volume, minimum-maximum frontal width, and frontal bone surface length) differed significantly between the genders (P